2005
DOI: 10.1109/tdmr.2005.853453
|View full text |Cite
|
Sign up to set email alerts
|

Temperature stability of ZnO thin film SAW device on fused quartz

Abstract: Surface acoustic wave (SAW) filters for lowfrequency (38-65 MHz) applications have been developed using a radio frequency (RF)-magnetron-sputtered ZnO film on fusedquartz substrates. SAW propagation characteristics such as electromechanical coupling coefficient (K 2 ), SAW phase velocity (v), insertion loss, and temperature coefficient of delay (TCD) have been measured. The intergidital transducer (IDT)/ZnO/fusedquartz device structure yields almost zero TCD (1 ppm · • C −1 ) with 0.316 λ thick ZnO layer (for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…8,9 In most of these studies, the presence of stress in the deposited ZnO films has been identified as a critical parameter and may affect the performance of the devices due to change in electrical and optical properties. [2][3][4][5][6][7][8][9] Various deposition techniques are being used to grow highly c-axis oriented zinc oxide thin films and each technique has its own advantages and disadvantages. 1 The rf magnetron sputtering is found to be the most suitable technique due to better control over stoichiometry and deposition of uniform film.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In most of these studies, the presence of stress in the deposited ZnO films has been identified as a critical parameter and may affect the performance of the devices due to change in electrical and optical properties. [2][3][4][5][6][7][8][9] Various deposition techniques are being used to grow highly c-axis oriented zinc oxide thin films and each technique has its own advantages and disadvantages. 1 The rf magnetron sputtering is found to be the most suitable technique due to better control over stoichiometry and deposition of uniform film.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of temperature on SAW propagation characteristics is typically characterized in terms of temperature coefficient of delay (TCD) given by [6,7]:…”
Section: Temperature Coefficient Of Delaymentioning
confidence: 99%
“…Since a 2 for the materials used in the present layered configurations were not available in the literature, we restrict our calculations to use a 1 only. The material constants and temperature coefficients used in the calculations have been reported in [7] and summarized in Table 1.…”
Section: Temperature Coefficient Of Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike many of its competitors, ZnO is inexpensive, relatively abundant, chemically stable, easy to prepare, non toxic and most of the doping materials that are used with it are also readily available. It has been used in a variety of applications such as conductive films, solar cell windows, photoelectric cells, nonlinear optics, bulk and surface acoustic wave devices [1][2][3], and micro mechanic devices [4,5]. ZnO wide band gap opens the possibility of creating ultraviolet (UV) light emission diodes (LEDs) and white LEDs with superior color purity.…”
Section: Introductionmentioning
confidence: 99%